SANITATION ENVIRONMENTAL DETERMINANTS WITH EVENTS OF DIARRHEA IN CHILDREN IN RESIDENTIAL SOLID WORK AREA HEALTH PUBLIC HEALTH CENTER RUMBAI PEKANBARU CITY - Rasyid, Zulmeliza; Meliyanti, Rezki; Susanti, Nurvi; Harnani, Yessi (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2017)
Diarrhea is a condition where a person defecating with soft or liquid consistency (three times or more) in one day. Pekanbaru City Health Department data obtained by the number of diarrhea cases in Puskesmas Rumbai handled in 2013 totaled 670 cases (28%), the year 2014 amounted to 827 cases (35%). The purpose of this study is Knowledgeable picture and determinants of environmental sanitation with the incidence of diarrhea in infants in the densely populated area Puskesmas Rumbai Pekanbaru This type of research is an analytic-quantitative with cross sectional design. The sample amounted to 102 infants. Methods of data collection is done by interviews and data collection tools were questionnaires. Quota sampling using sampling techniques. Computerized data processing. The data analysis univariate and bivariate with chi-square test. The results were obtained landfills value of p = 0.001 and OR = 3.13, waste water management, with p = 0.004 and OR = 3.60, type of latrine with a value of p = 0.002 and OR = 5.60, the distance means clean water cesspools with p = 0.001 and OR = 10.29. So we can conclude all the variables associated with the incidence of diarrhea in the densely populated area Puskesmas Rumbai Pekanbaru It is expected that the health center Rumbai Pekanbaru doing outreach to the community about the importance of environmental sanitation hygiene so that children are not susceptible to diarrheal diseases.